SISTEM NOTIFIKASI AGENDA HARIAN MENGGUNAKAN APPLICATION PROGRAMMING INTERFACE (API ) DAN SMS GATEWAY - Imam Prasetyo; Joko Triyono; Dina Andayati (Jurnal Jarkom, 2016)
At this moment, the density of someone’s own activities are not infrequently missing or forgetting to do. The Indonesian people use the book to record the important things. One of the most book types used to record is the schedule book. As the development of technology, having a digital reminder with an accurate time frame is one of eases desired many people, by using social media, sms gateway and computer technology, a notification daily schedule reminder application is made acceptable and readed using social media or SMS. This application is expected to reduce the difficulty of the client which is usually recorded in the schedule book, if the book is lost, the notes will be lost and if recorded in a mobile phone and switch the phone then records which are crucial going to be lost too.This research uses computer technology by utilizing a database server MySQL, HTML5, PHP5, CSS, JavaScript, API (facebook, twitter and whatsapp), gammu and crontab. The methods used in this research are observation, a study literature and experiment. The system uses five tables to store client, sub client and schedule data, the tables are: user, alamat_notif, pesan, penerima and h_pesan. The conclusions can be taken based on the research are: API whatsapp and API facebook chat cannot be used, the sending of messages management to the notification media can be done in accordance with priorities and time that has been determined, the sending of messages media can be done in twitter, email and sms, crontab in the research used to run php file, so the sending of messages can be done automatically, and crontab begin to walk at range of time 0 to 2 seconds.